Prisoners’ information dissemination by national central library in Tanzania: Challenges and the way forward - Kotoroi, Gladness L.; Tukae, Nancy E. (Serial librarian, 2024)
A research paper submitted to the serial librarian, volume.83, No. 2 of 2022, Pg.128-140.